Understanding and measuring social capital : a multidisciplinary tool for practitioners - Grootaert, Christiaan, 1950-; Van Bastelaer, Thierry (Directions in development (Washington, D.C.), 2002)
Understanding and Measuring Social Capital details various methods of gauging social capital and provides illustrative case studies from Mali and India. It also offers a measuring instrument, the Social Capital Assessment Tool, that combines quantitative and qualitative approaches. This tool can be downloaded from a CDROM which is included with the book.